(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The sector is also facing increased demands from the availability of labor to inefficient resource utilization. This project presents a self-guiding IoT-powered robot for irrigating crops. It utilizes with help the mobile robot frame and its control via the Arduino framework. The decision-making mechanism in the system enables automated irrigation based on soil condition, and the ultrasonic sensors provide collision detection for obstacle avoidance when moving through the farm. Environmental information transmits wirelessly and allows the farmer to monitor the field from anywhere. Experiments under the controlled agricultural environment revealed that the robot operates effectively, with accuracy of soil moisture measurement above 92%, and there is up to a 28% traditionalmethods. This project provides a low-cost approach for adopting precision agriculture techniques, particularly suitable for small to medium-sized farms. Future developments can focus on using machine learning algorithms to predict plant health and GPS for navigation.